The Metrics of the DMA’s Success - Giuseppe Colangelo; Alba Ribera Martínez (European Journal of Risk Regulation)
The Digital Markets Act (DMA) is a rare bird in competition policy. Indeed, it is a hybrid framework incorporating the institutional setting of a regulatory tool as well as the conduct already targeted by antitrust authorities in proceedings against digital platforms. From a policy perspective, the DMA seeks to prevent some anticompetitive practices. To this end, the EU legislator has construed an intricate set of provisions pursuing different policy goals. After setting out these goals in relation to the proclaimed legal interests protected by the DMA (ie, contestability and fairness), the paper uncovers the policy goals underlying each of the provisions. Relying on the first round of compliance reports issued by gatekeepers in March and October 2024, the analysis aims at providing adequate pathways to measure the DMA’s success, based on the explicit legal interests and implict policy goals fleshed out by the regulation. The paper maps out market scenarios where policymakers can assert that the DMA’s enforcement has been effective.